Experimental study on seismic performance of the connection for ATLS modular house. (July 2020) - Zhang, Jun-Feng; Tian, Guang-Feng; Zhao, Jun-Jie; Deng, En-Feng; Wen, Ming-Gang; Ye, Lin; Guo, Xin-Sheng; Zhou, Ji-Jian; Wang, Shi-Quan; Xing, Xu-Ying
Abstract: Modular steel constructions (MSCs) have been widely used for buildings with repetitive units and a lot of research demonstrated that the overall structural performance was highly influenced by the connection between the modules. Due to the special configuration, the connection for assemble-type of light-steel modular house (ALTS modular house) was more complex than ordinary MSCs. In order to study the seismic performance of connection for ATLS modular house, three specimens were designed and tested under different axial load in this paper. The failure mode and seismic performance of the connection were evaluated and discussed in detail based on the test results. In addition, the load-transferring mechanism of the column were explored by strain monitoring. Three failure modes of connection were found. The ultimate bearing capacity, stiffness degradation, and energy dissipation of the connection were significantly influenced by the axial load. Further, a three-dimensional (3D) nonlinear finite element model (FEM) was established by the general-purpose finite element software ABAQUS. The failure mode and hysteretic curves were in good agreement with the test results and the FEM can be adopted for the analysis of the seismic behavior of the connection. Highlights: Three connection specimens for ATLS modular house were tested. The seismic performance of the connection was obtained and evaluated. The connection meets the requirements of current design code. Finite element model was established and verified against the test results.